Partial purification and characterization of uricase from a thermophilic pseudomonas sp - Hamid Reza Mansouri Khosravi, 1983- author; Shafinaz Shahir; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2013